Self-report demands of patients referred to social workers in Taleghani hospital, Tehran - Lak, Mehran; Rashidi, Mohammad Mahdi; Kolahi, Ali-Asghar (Social Determinants of Health, 2017)
Background: Social workers have a responsibility to tackle the social determinants of health which cause health inequities. The hospitals’ social work units have the responsibility to improve patients’ physical, mental, and social health. In this regard, understanding patients’ demands is essential. The objective of the present study was to determine self-report demands of patients who were referred to social work unit in Taleghani hospital, Tehran. Methods: The current cross-sectional study was conducted on the clients who were referred to social work unit of Talghani hospital, Tehran. Data was collected during autumn 2015 using convenience sampling method. Data collection form included demographic characteristics of the participants, the reason for referral to the social worker, self-report demands of the patients, and the response of the social worker to the patients. Data was analysed using IBM SPSS Statistics for Windows, Version 22.0. Results: Of all clients who had attended social work unit, 772 accepted to participate in the study (response rate 87.1%). About 43% of the patients were female. Out of 990 requests, about 50% of the clients needed assistance to resolve financial problems. Help for resolving familial and insurance problems were the subsequent demands of the clients. Meanwhile, the most common response given by the social worker to the patients’ demands was financial assistance (n=276) (28.9%), and helping to resolve patient’s familial problems (n=107) (11.2%) and offering health insurance services (n=106) (11.1%) were the second and the third most common responses, respectively. Conclusion: The present study showed that still we have a long way to meet the aims of social work unit for empowering the patients and their families to withstand difficult conditions following the disease.